Influência das temperaturas constantes e flutuantes sobre as características biológicas de Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) em gerações sucessivas - Barrufaldi, Ana Paula Frugeri [UNESP] (2015)
This study aimed to evaluate the temperature on the biological aspects of Euschistus heros during three successive generations. Six constant temperatures were used (19ºC, 22ºC, 25ºC, 28ºC, 31ºC and 34ºC ± 1°C), four floating temperatures (day:night) (25:21 ° C, 28:24 ° C, 31:27 ° C, 34:30 ° C ± 1°C) and relative humidity 70 ± 10% in all treatments. Each temperature had six replications of 20 individuals each. The evaluation of the nymphal stages was daily and later, adults were separated by sex and the weight (mg) and the pronotum (mm) of individuals were evaluated. After the formation of couples, eggs were collected the preoviposition period, total number of eggs and egg viability. The increase in temperature caused reduction in the duration of nymphal stages of E. heros. The smallest constant temperature (19°C), increased the period of insect nymphal stages and there was no survivors for the next generations, and was evaluated by three successive generations. The constant temperature of the upper end (34°C) did not influence the nymphal viability of E. heros, however, reduced the adults longevity. In floating temperatures, the nymphal viability did not differ between treatments; however all were higher than the constant 19°C. The extremes temperatures of 19°C and 34°C the development of insects were not suitable, so there were no subsequent generations. This study showed that the increased temperature from 22°C to a maximum of 28°C favored the E. heros biology.